THE PECULIARITIES OF COLORS IN PAINTING AND ITS EFFECT ON HUMANS. (Лучшие интеллектуальные исследования, 2025)
Abstract: this article will talk about the types of colors used in painting, the effect of colors on humans and its proper use.